Quantum Field Theory of black hole perturbations with backreaction. Part II. Spherically symmetric 2nd order Einstein sector - Neuser, Jonas; Thiemann, Thomas (Journal of Cosmology and Astroparticle Physics, 2025)
In this second paper of our series we focus on the classical pure gravity sector of spherically symmetric black hole perturbations and expand the reduced Hamiltonian to second order. To compare our manifestly gauge invariant formalism with established results in the literature we have to translate our results derived in Gullstrand-Painlevé gauge to the gauges used in those works. After several canonical transformations we expectedly find exact agreement with the Hamiltonian given by Moncrief which generates the Regge-Wheeler and Zerilli equations of motion for the linear axial (often denoted odd) and polar (often denoted even) perturbations respectively. This confirms the validity of our method which includes backreaction and easily generalises to higher orders.
CRIS-Team Scopus Importer:2025-01-31
Keywords: GR black holes; gravitational waves / theory; quantum black holes